Evaluating the Effects of the Latest Crises on the Willingness and Understanding of Cross-Border Cooperation - Medeiros, E.; Santamaria. J. T.; Martín Guillermo Ramírez (Third ABS World Conference, 2023)
This paper aims to present the preliminary results of a survey to be implemented by the Association of European Border Regions (AEBR) among its members. It will take place in September-October 2022 to ask border regions — sub-national public authorities — and cross-border structures — euroregions, eurodistricts, eurocities, European Grouping of Territorial Cooperation (EGTCs), etc. — about the extent to which the various series of crises faced in the last years have affected their willingness and understanding of cross-border cooperation and the “open borders” paradigm. For that, we will use two sets of questions: 1) general topics, such as the effects of COVID-19, the refugees’ crises and migration phenomena, the rise of populism and the need to react effectively to global warming. 2) specific topics for specific actors, such as the effects of Brexit in Ireland, the consequences of the Ukrainian war in Eastern European border regions, and the transition to greener sources of energy in traditional coal producer’s areas. In order to get a further level of answers, we will also promote a “cascade effect”, asking for someone else in everyone’s circle to further or better respond to any of the questions. The questions posed in this call for papers have resulted indeed very inspiring to better shape our survey, which is seeking to present a general trend of different transformations linked to cross-border cooperation and regionalism. Therefore, we will explore how rebordering is challenging local and regional stakeholders’ cross-border strategies, and how they handle opposite border discourses. We also plan to inquire how they are facing demographic, energy and digital transitions.